THE ROLE OF PERSONALITY TRAITS AND MOOD IN TASTE PREFERENCE AMONG UNIVERSITY STUDENTS - Khan, Saira; Arif, Habiba; Shahzadi, Neelum; Iqbal, Muhammad Maqsood (Journal of Pakistan Psychiatric Society, 2022)
Objective: The current study was conducted to investigate the relationship between personality traits, mood and taste preference among university students. Design: Correlational and Cross-sectional research design was used for the present study. Method: The sample was comprised of 170 university students, 83 males and 87 females with age range 18-25 years. The sample size was calculated through G*power. Data was collected online through google form. The Big Five Inventory-10, Brief Mood Introspection and a self-constructed taste preference scale were used to assess personality traits, mood and taste preference respectively. Results: The results suggested that some specific personality traits were correlated with specific taste preferences such as agreeableness was associated with salty, sour, and sweet taste preferences while negatively associated with bitter taste preference. As well as extraversion was significantly positively associated with salty taste preference. On the other hand, pleasant mood was also shown to have positive correlation with salty, sweet, spicy, and sour taste preference. The finding of current research also showed that women are more likely to prefer salty, spicy, and sour tastes than men. Conclusion: There are some specific mood and personality traits that are related with specific taste preferences. Gender differences indicated that women are more likely to prefer food on the basis of its taste while men are more likely to prefer food on the basis of amount of its calories. Implication: The present research would be useful in health settings in order to design diet plans for obese individuals according to their personality, mood and related food choices.